Bacteriological Profile and Antibiotic Susceptibility Pattern in Sterile Body Fluids from a Tertiary Care Hospital in Bhubaneswar, Odisha, India: A Cross-sectional Study - Shreekant Tiwari; Monalisah Nanda; Swetalona Pattanaik; Anju Prasad; Amruta Kar; Sarita Kumari Nayak; Neha Patnaik; Deepika Mamidi (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Sterile body sites are those where no microorganisms exist as commensals in an otherwise healthy person. Isolation of microorganisms from these sites can indicate either pathological agents or contaminants from the skin. Sterile body fluids are frequently received in microbiology laboratories for culture and sensitivity testing, as the isolation of pathogens from these sites is associated with significant mortality and morbidity. Aim: To assess the current scenario of aerobic bacteriological profiles and their antibiotic susceptibility patterns in various sterile body fluids at a tertiary care hospital in Bhubaneswar, Odisha, India. Materials and Methods: A hospital-based observational study was conducted in the Department of Microbiology at a Tertiary Care Hospital in Bhubaneswar, Odisha, India. The study duration was one year, from January 2022 to December 2022. A total of 450 body fluid samples were collected from 567 patients, of which 117 samples did not meet the inclusion criteria. Out of the 450 samples, 315 were from male patients and 135 were from female patients. All infected body fluids received from clinically diagnosed cases, irrespective of age and gender, were included. Antimicrobial susceptibility testing was performed using the Kirby-Bauer disc diffusion method following the guidelines of the Clinical Laboratory Standards Institute (CLSI). Sterile body fluids were collected with complete aseptic precautions and processed in the Department of Microbiology using standard laboratory procedures. Statistical data analysis was conducted using MS Excel and Statistical Package for Social Sciences (SPSS) version 27.0. A p-value <0.05 was considered statistically significant. Results: A total of 450 clinical samples were processed, of which 153 (34%) were peritoneal fluid, 92 (20.5%) were synovial fluid, 77 (17.1%) were pleural fluids, 118 (26.2%) were Cerebrospinal Fluid (CSF), and 10 (2.2%) were pericardial fluid. In the present study, 126 (28%) pathogens were isolated from the 450 processed samples, with gram negative bacilli being the predominant isolates (88/126, 69.8%), while the remaining 38/126 (30.2%) were gram-positive isolates. Among the 88 gram negative isolates, Escherichia coli was the most common (27, 21.4%), followed by Klebsiella pneumoniae (23, 18.2%), Pseudomonas aeruginosa (14, 11.1%), Acinetobacter spp. (12, 9.5%), Enterobacter spp. (7, 5.6%), and Citrobacter spp. (5, 4.0%). Similarly, among the gram-positive isolates, Staphylococcus aureus was the most common (20, 15.9%), followed by Coagulase-Negative Staphylococci (CONS) (16, 12.7%) and Enterococcus spp. (2, 1.6%). Gram negative isolates showed 100% sensitivity to colistin and polymyxin B, followed by imipenem (90%) and cefepime (80%). Grampositive isolates exhibited 100% sensitivity to linezolid, followed by vancomycin. Conclusion: Early identification of pathogens from these sites, along with their antibiotic susceptibility patterns, will help clinicians initiate targeted therapy. This approach can reduce hospital stays for patients and minimise the development of drug resistance.